SENSORS AND SMART GARMENTS FOR ARTHRITIS PATIENTS: A COMPREHENSIVE STUDY AND FUTURE DIRECTIONS - Safal Choudhary; Sampath Kumar; Shiva Prasad H.C; Princy Randhawa (Proceedings on Engineering Sciences)
Arthritis, being a chronic condition, significantly impacts the quality of life experienced by those affected by it. This enduring illness poses ongoing challenges that can hinder daily activities and diminish overall well being. This study delves into the multifaceted challenges encountered by arthritis patients, exploring the functionality of different sensors used to treat joint pain and other arthritis symptoms . This study innovativel y explores the multifaceted functionality of sensor and smart garment technologies in arthritis management, t he purpose of this study is to investigate the effectiveness of various sensors and smart garments in managing arthritis symptoms, their applicatio ns, and their limitations. Through a comparative study, this study offers an extensive analysis of sensors and smart garments . It delves deeply into the subject matter to provide comprehensive insights into the topic at hand, it presents a thorough underst anding and highlights significant findings of current studies in sensor and smart garment technologies and their implementations, this study aims to discuss the design solutions and usability of smart garments tailored for arthritis management. Additionall y , it seeks to bridge existing gaps in knowledge regarding the integration of sensors and uses for overall arthritis management. The findings of this study contribute t o a deeper understanding of how sensor technology can be harnessed to improve the quality of life for arthritis patients. The originality and value of this study lie in its comprehensive study of sensor technologies in the context of arthritis management, offering insights that can guide future research and the development of innovative smart garment solutions that address the specific needs of arthritis patients while enhancing their overall quality of life.